2020
DOI: 10.1186/s13071-020-3930-9
|View full text |Cite
|
Sign up to set email alerts
|

Ingested insecticide to control Aedes aegypti: developing a novel dried attractive toxic sugar bait device for intra-domiciliary control

Abstract: Background: Illnesses transmitted by Aedes aegypti (Linnaeus, 1762) such as dengue, chikungunya and Zika comprise a considerable global burden; mosquito control is the primary public health tool to reduce disease transmission. Current interventions are inadequate and insecticide resistance threatens the effectiveness of these options. Dried attractive bait stations (DABS) are a novel mechanism to deliver insecticide to Ae. aegypti. The DABS are a high-contrast 28 inch 2 surface coated with dried sugar-boric ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Houses in good repair limit exposure to mosquitoes, and the association between substandard housing structure and arboviral risk has been repeatedly documented in locations beyond Ecuador [49][50][51]. Houses made of cane were a risk factor for dengue, which is consistent with typical housing found in low income areas with active dengue transmission in Ecuador [52]. Generally found in the urban periphery of Machala, housing constructed from cane does not exclude potentially infectious mosquitoes from entering households [12].…”
Section: Resultssupporting
confidence: 53%
“…Houses in good repair limit exposure to mosquitoes, and the association between substandard housing structure and arboviral risk has been repeatedly documented in locations beyond Ecuador [49][50][51]. Houses made of cane were a risk factor for dengue, which is consistent with typical housing found in low income areas with active dengue transmission in Ecuador [52]. Generally found in the urban periphery of Machala, housing constructed from cane does not exclude potentially infectious mosquitoes from entering households [12].…”
Section: Resultssupporting
confidence: 53%
“…Later, the same results were reported with an even lower concentration of boric acid (0.1%) in TSB solution against Aedes mosquitoes after 10 days exposure in laboratory 4 . Thereafter, several studies were undertaken with boric acid and sugar solution against Aedes and Culex mosquitoes, and > 90% mortality was observed after 48 h exposure under controlled conditions 15, 30, 39, 40 . Although the majority of studies reported significantly high mortality rates of Aedes mosquitoes with boric acid, a few recent studies documented relatively less mortality (50–70%) 23, 24, 33 .…”
Section: Toxicants Used In Atsbmentioning
confidence: 60%
“…A study in Ecuador was recently conducted with dried ATSB and showed that this may have better implications for vector control 39 . However, a major shortcoming of current ATSB strategies is the use of fruit juice as an attractant.…”
Section: Future Research Challengesmentioning
confidence: 99%
See 2 more Smart Citations